Designing and Building an Irrigation Management Information System Using the Prototype Method - Kafi, Rizal; Zulfikar, Zulfikar (NEWTON: Networking and Information Technology, 2025)
In the current system, agricultural extension workers manually collect and summarize extension outcome data using spreadsheets (Microsoft Excel). The weaknesses of this manual system are errors in data entry, duplicate data, and a rather long time for recapitulation. This research aims to develop and implement a web-based Irrigation Management Information System that is integrated and easy for agricultural extension workers at the sub-district level to use. The method used in this research is Research and Development, with a prototype model that allows interaction between developers and users during the creation process. The results of functional testing on this system show that the system has met user needs and no errors were found in any of the functions. Additionally, the limited trial involved 35 users who rated the system as very easy to use. It is hoped that with this irrigation management information system, water resource management can be carried out more effectively, supporting agricultural productivity and the overall well-being of farmers.